The value of cotton seed meal as a stock food - Jones, Charles Sumner (My University, 1906)
Introduction: The three most important principles which must be supplied in stock feed are protein, carbohydrates and fat. In most feeds fed today the two latter principles can be very easily supplied in feeds such as corn, which is the most universal feed used today, but this feed is very poor in protein which is a very important part of a ration and which costs the most. But the part of the feed which must be supplied to a feeding ration if a balanced rat ion is to be fed. The balanced ration rot only causes the animal to make better gains when in the feed lot but also keeps them in better health and they are more resistant to disease. The problem then that confronts the stockmen is, How can protein be added to the feed with a minimum cost. Linseed Meal, bran, and dried blood contain a large percent of this substance, but on account of the great demands for these substances, the price has risen so high that the average stockmen cannot afford to feed them. So some other source must be resorted to, and here is where cotton seed meal comes in to help out the stockmen. This meal is made every year in large Quantities at the southern oil mills and can be bought at a moderate price, about $25 per ton. No other food contains as much digestible protein pound for pound as does cotton seed meal. So if cotton seed meal does cost as much as oil meal or some of the other protein feeds it will pay to buy the cotton seed meal as we get much more protein than we would in the same weight of oil meal. Recent experiments have been conducted in feeding this concentrated feed to various domestic animals. The results of some of some of the most recent work along this line will be given in the following lines. Also some of the most recent conclusions reached in regard to the value of Cotton seed meal as a stock food.
Citation: Jones, Charles Sumner. The value of cotton seed meal as a stock food. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Cotton Seed Meal; Animal Husbandry; Stock Food; Theses